2004
DOI: 10.1258/1357633042614339
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a radiology information system/picture archiving and communication system and an image transfer system at a large public teaching hospital — assessment of success of adoption by clinicians

Abstract: In 2001 a radiology information system/picture archiving and communication system (RIS/PACS) was installed at the Princess Alexandra Hospital (PAH) in Brisbane, with electronic image transfer links to other major hospitals in Queensland. An assessment study is being performed of the effect of the ready availability of radiology results on clinicians, clinical decision making and the time taken to treat patients. A series of structured interviews with senior clinicians at the PAH began in July 2002. Administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…The current study did not reveal a corresponding significant reduction in LOS (Table 1). This finding is similar to those reported by others [2,14,15]. …”
Section: Discussionsupporting
confidence: 93%
“…The current study did not reveal a corresponding significant reduction in LOS (Table 1). This finding is similar to those reported by others [2,14,15]. …”
Section: Discussionsupporting
confidence: 93%
“…This shift relates to the technology development and to new routines in practice. Crowe and Sim (2004) have studied the effect of the ready availability of radiology results on clinicians, clinical decision making and the time taken to treat patients at a large teaching hospital in Brisbane. This study showed that the introduction of RIS/PACS has been well received by senior clinicians and it has been helpful in clinical decision making.…”
Section: The Impact Of Pacs On Radiological Workmentioning
confidence: 99%
“…Radiographers then saw a great potential in the introduction of new routines using PACS. Crowe and Sim (2004) have studied the effect of the ready availability of radiology results on clinicians, clinical decision making and the time taken to treat patients at a large teaching hospital in Brisbane. This study showed that the introduction of RIS/PACS has been well received by senior clinicians and it has been helpful in clinical decision making.…”
Section: The Impact Of Pacs On Radiological Workmentioning
confidence: 99%
“…Ethnographic research method has become useful in understanding the organization of health care (Barley, 1986;Crowe & Sim, 2004;Karasti, 1998;2000& Smith et al 2003. The method can provide a nuanced understanding of an organization and allow comparison between what people say and what they do.…”
Section: Ethnography In Health Carementioning
confidence: 99%